Penile Reconstruction with Skin Grafts and Dermal Matrices: Indications and Management - Paloma Triana Junco; Mariela Dore; Vanesa Nuñez Cerezo; Javier Jimenez Gomez; Miriam Miguel Ferrero; Mercedes Díaz González; Pedro Lopez-Pereira; Juan Carlos Lopez-Gutierrez (Georg Thieme Verlag KG, 2017)
Abstract Introduction The penis eventually needs specific cutaneous coverage in the context of reconstructive procedures following trauma or congenital anomalies. Local flaps are the first choice but are not always available after multiple previous procedures. In these cases, skin graft and dermal matrices should be considered. Materials and Methods This study was a retrospective review of the past 4 years of four patients with severe loss of penile shaft skin who underwent skin reconstruction. Dermal matrices and skin grafts were utilized. Dermal matrices were placed for a median of 4.5 weeks (3.0-6.0 weeks). The skin graft was harvested from the inner thigh region for split-thickness skin graft (STSG) and the inguinal region for full-thickness skin graft (FTSG). Results The four patients presented with complete loss of skin in the penile shaft. One patient had a vesical exstrophy, one had a buried penis with only one corpus cavernosum, one had a wide congenital lymphedema of the genitalia, and one had a lack of skin following circumcision at home. They underwent reconstruction with three patients undergoing split-thickness skin graft; two dermal matrices; and one full-thickness graft, respectively, thereby achieving a good cosmetic and functional result. There were no complications, and all the patients successfully accepted the graft. Conclusion Dermal matrices and skin grafts may serve as effective tools in the management of severe penile skin defects unable to be covered with local flaps.